Marketing mix and STP strategies: an exploratory study into grocery retailers in Malaysia - Phang Ing @ Grace; Zaiton Osman; Yin, Lim Tze (Human Resource Management Academic Research Society (www.hrmars.com), 2020)
The purpose of this paper is to obtain insights on the grocery retailer, by comparing across three retail formats (e.g. supermarket, minimarkets and convenience store) in Malaysia, and exploring how these local grocery retailers segment, target, position (STP Strategies) and plan for their marketing mix strategies. In order to investigate the experience shared among the retailers, the interview has been conducted, and textual analysis focused on comparing the similarities and differences in retail strategies has been adopted. The data were transcribed and analysed using content analysis with the aid of Quirkos software. The findings of the paper provide an alternative perspective for the retailers and marketers towards the importance of STP and marketing mix strategies in the grocery retail industry. The paper also demonstrates the extension in the current marketing literature, which address the crucial contribution of STP and marketing mix strategy in the marketing discipline.